2015
DOI: 10.1523/jneurosci.2542-15.2015
|View full text |Cite
|
Sign up to set email alerts
|

Mindfulness Meditation-Based Pain Relief Employs Different Neural Mechanisms Than Placebo and Sham Mindfulness Meditation-Induced Analgesia

Abstract: Mindfulness meditation reduces pain in experimental and clinical settings. However, it remains unknown whether mindfulness meditation engages pain-relieving mechanisms other than those associated with the placebo effect (e.g., conditioning, psychosocial context, beliefs). To determine whether the analgesic mechanisms of mindfulness meditation are different from placebo, we randomly assigned 75 healthy, human volunteers to 4 d of the following: (1) mindfulness meditation, (2) placebo conditioning, (3) sham mind… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

19
281
3
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 301 publications
(305 citation statements)
references
References 87 publications
19
281
3
2
Order By: Relevance
“…Other active group-based interventions have been effectively implemented, ranging from relaxation interventions (Creswell et al 2016) to targeted health education programs (Morone et al 2016). The brief mindfulness intervention literature (consisting of interventions that last two weeks or less) also offers a number of well-matched active control interventions, ranging from attention control training programs (e.g., listening to the same guided mindfulness exercise with the instruction to count the number of verbs) (Koole et al 2009, Schofield et al 2015, to placebo conditioning (Zeidan et al 2015), and health education interventions (Mrazek et al 2013). One intriguing new approach in the brief mindfulness interventions literature offers sham mindfulness meditation training where participants are instructed periodically "to take a deep breath as we sit here in mindfulness meditation" without any explicit instructions on how to foster mindful awareness (Zeidan et al 2015).…”
Section: Internet and Smartphone Application Mindfulness Interventionsmentioning
confidence: 99%
See 3 more Smart Citations
“…Other active group-based interventions have been effectively implemented, ranging from relaxation interventions (Creswell et al 2016) to targeted health education programs (Morone et al 2016). The brief mindfulness intervention literature (consisting of interventions that last two weeks or less) also offers a number of well-matched active control interventions, ranging from attention control training programs (e.g., listening to the same guided mindfulness exercise with the instruction to count the number of verbs) (Koole et al 2009, Schofield et al 2015, to placebo conditioning (Zeidan et al 2015), and health education interventions (Mrazek et al 2013). One intriguing new approach in the brief mindfulness interventions literature offers sham mindfulness meditation training where participants are instructed periodically "to take a deep breath as we sit here in mindfulness meditation" without any explicit instructions on how to foster mindful awareness (Zeidan et al 2015).…”
Section: Internet and Smartphone Application Mindfulness Interventionsmentioning
confidence: 99%
“…The brief mindfulness intervention literature (consisting of interventions that last two weeks or less) also offers a number of well-matched active control interventions, ranging from attention control training programs (e.g., listening to the same guided mindfulness exercise with the instruction to count the number of verbs) (Koole et al 2009, Schofield et al 2015, to placebo conditioning (Zeidan et al 2015), and health education interventions (Mrazek et al 2013). One intriguing new approach in the brief mindfulness interventions literature offers sham mindfulness meditation training where participants are instructed periodically "to take a deep breath as we sit here in mindfulness meditation" without any explicit instructions on how to foster mindful awareness (Zeidan et al 2015). This sham mindfulness procedure has been effective in controlling for positive treatment expectancies in studies, yet does not show the same pain relief benefits as actual mindfulness meditation training (Zeidan et al 2010b(Zeidan et al , 2015.…”
Section: Internet and Smartphone Application Mindfulness Interventionsmentioning
confidence: 99%
See 2 more Smart Citations
“…Studies have shown mindfulness to activate the areas associated with pain management, such as the orbit frontal and cingulated cortices reduce cortisol levels and improve neuroendocrine responses to psychosocial stress [12][13][14]. Lazar et al, tested the hypothesis that regular meditation practice is associated with differences in the structures in the brain and with magnetic resonance imaging determined the thickness of the cerebral cortex of experienced meditators to be significantly different than non-meditators (significance, p<0.001) [15].…”
mentioning
confidence: 99%